Effect of an incentive-led intervention to address the shortage of village health workers in China: a community-based, non-randomised controlled trial. (December 2017) - Hesketh, Therese; Wang, Weiyi; Xu, Yannan; Zhou, Xudong
Abstract: Background: Problems with recruitment and retention of village doctors have led to shortages in many parts of rural China. The situation has been deteriorating since 2009, when health reforms led to an increase in patient flow to township facilities, reducing village clinic attendance and doctors' income. We aimed to assess an intervention to reverse the decline in village doctor numbers in Jiangshan County, Zhejiang province. Methods: This community-based prospective, non-randomised controlled trial was done across Jiangshan County, Zhejiang province, between January, 2012, and December, 2014. Our intervention group consisted of village clinics in Jiangshan County who voluntarily agreed to join the intervention group during the course of the study, with the remainder serving as controls. Clinics joined the intervention in a stepwise fashion: 17 in February, 2012, 17 in December, 2012, five in June, 2013, 47 in October, 2013, ten in January 2014, and eight in November, 2014. 104 village clinics (including five newly built clinics) had joined the intervention by the end of 2014. The remaining 83 village clinics served as controls. The intervention consisted of four components: (1) shift of the village clinic from private to collective ownership; (2) payments by local government to village doctors of ¥800 RMB per month, plus ¥4 RMB per patient visit; (3) introduction of a ¥5 RMB consultation fee, covered by health insurance; and (4) introduction of the zero-profit essential drug list (as in township hospitals) to discourage overprescribing and encourage patient attendance. Clinic records and doctors' views regarding job satisfaction and trust by patients, assessed by face-to-face interview, were compared at baseline and 36 months after initiation of the intervention. We obtained ethics approval from Zhejiang University, and participants gave oral informed consent. Findings: Our sample consisted of 104 village doctors working at 104 clinics who received the intervention and 83 doctors at 83 clinics who did not (controls). In the 64 intervention clinics for which we had data for January to December, 2014 (the final year of assessment), patient visits increased from an annual mean of 2494 (SD 1214) per clinic in the year preceding baseline to 4316 (1223) in the final year of assessment (mean difference vs 40 controls, 2163; p<0·0001). Doctors' mean income increased from ¥44 900 RMB (SD ¥13 700) at baseline to ¥63 500 RMB (¥16 000) in the final year of assessment and the mean cost per visit fell from ¥50 RMB (SD 14) to ¥32 RMB (7). In the 64 intervention clinics analysed, the proportion of patients who were prescribed antibiotics or intravenous injections out of all attending patients, per patient visit, reduced from 69% to 44% (difference vs 40 controls 30·2%; p<0·0001), and 71% to 49% (difference vs controls 16·5%; p<0·0001), respectively. Between baseline and 36 months, 28 clinics opened in villages previously without a doctor. Of 64 doctors randomly selected for interview in intervention village clinics, 53 [83%] were very satisfied with the intervention, 49 (77%) were very satisfied with their income, 47 (73%) thought patient care had improved, and 55 (86%) thought that the doctor–patient relationship had improved. All the control clinics in Jiangshan have since joined the intervention. Interpretation: In areas of rural China where local government can provide the necessary resources, the model we describe can address the shortfalls in health services at the village level. Funding: Zhejiang University Zijin Talent Programme.